1999
DOI: 10.1103/physrevb.59.15464
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron x-ray-diffraction study of the structure and growth of Xe films adsorbed on the Ag(111) surface

Abstract: Synchrotron x-ray scattering has been used to investigate the structure and growth of perhaps the simplest of all films: xenon physisorbed on the Ag͑111͒ surface. High-resolution x-ray scans of the in-plane structure and lower-resolution scans ͑specular and nonspecular͒ of the out-of-plane order were performed. The Xe films were prepared under both quasiequilibrium and kinetic growth conditions, and have fewer structural defects than those investigated previously by others on graphite substrates. Under quasieq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…Their origin appears to be dislocations in the layers, which are most prevalent at the highest temperatures studied, as expected for entropic reasons. This is consistent with x-ray diffraction studies of the growth of Xe on Ag(111), where stacking faults were observed for Xe growth under various growth conditions [24,25], although the overall structure observed was fcc(111). Such a stacking fault is evident in Figure 5, which shows a superposition of Xe layers 2 and 4 at point e in Figure 2.…”
supporting
confidence: 88%
“…Their origin appears to be dislocations in the layers, which are most prevalent at the highest temperatures studied, as expected for entropic reasons. This is consistent with x-ray diffraction studies of the growth of Xe on Ag(111), where stacking faults were observed for Xe growth under various growth conditions [24,25], although the overall structure observed was fcc(111). Such a stacking fault is evident in Figure 5, which shows a superposition of Xe layers 2 and 4 at point e in Figure 2.…”
supporting
confidence: 88%
“…The adsorption height of Xe on Ag(111) has been studied experimentally using low-energy electron diffraction (LEED) 69 and synchrotron x-ray scattering 70 , both assuming bulk truncation of the metal surface. Adsorption energetics have been studied using temperatureprogrammed desorption (TPD) 71,72 and data from inelastic helium scattering 73 .…”
Section: Resultsmentioning
confidence: 99%
“…Table I shows the optimal adsorption distance and energy using PBE and HSE as underlying exchangecorrelation functionals whereas Figure 1 depicts the binding curve with the HSE+vdW surf and HSE+MBD methods. The adsorption height of Xe on Ag(111) has been studied experimentally using low-energy electron diffraction (LEED) 69 and synchrotron x-ray scattering 70 , both assuming bulk truncation of the metal surface. Adsorption energetics have been studied using temperatureprogrammed desorption (TPD) 71,72 and data from inelastic helium scattering 73 .…”
Section: Resultsmentioning
confidence: 99%
“…In the case of layer-by layer growth, characteristic intensity oscillations with the minimum intensity I min = 1 + A + B and the maximum intensity I max = 1 are observed as a function of the deposition time [15,19,20,21] (see Fig. 2).…”
Section: B In Situ Experimentsmentioning
confidence: 99%